Impact of proton pump inhibitors on the antiplatelet effects of clopidogrel - Sibbing, Dirk; Morath, Tanja; Stegherr, Julia; Braun, Siegmund; Vogt, Wolfgang; Hadamitzky, Martin; Schömig, Albert; Kastrati, Adnan; Beckerath, Nicolas von (Thrombosis and Haemostasis, 2009)
Patients receiving dual antiplatelet treatment with aspirin and clopidogrel are commonly treated with proton pump inhibitors (PPIs). Attenuating effects on platelet response to clopidogrel have been reported solely for the PPI omeprazole. PPIs differ in their metabolisation properties as well as their potential for drug-drug interactions. The aim of this study was to investigate the impact of different PPIs (pantoprazole, omeprazole, esomeprazole) on platelet response to clopidogrel in patients with previous coronary stent placement under chronic clopidogrel treatment. In a cross-sectional observational study, consecutive patients under clopidogrel maintenance treatment (n=1,000) scheduled for a control coronary angiography were enrolled. Adenosine diphosphate (ADP)-induced platelet aggregation (in AU*min) was measured with multiple electrode platelet aggregometry (MEA). From the entire study population, 268 (26.8%) patients were under PPI treatment at the time point of platelet function testing (pantoprazole, n=162; omeprazole, n=64; esomeprazole, n=42). Platelet aggregation (median [interquar-tile range]) was significantly higher in patients with omeprazole treatment (295.5 [193.5–571.2] AU*min) compared to patients without PPI treatment (220.0 [143.8–388.8] AU*min; p=0.001). Platelet aggregation was similar in patients with pantoprazole (226.0 [150.0–401.5] AU*min) or esomeprazole (209.0 [134.8–384.8] AU*min) treatment compared to patients without PPI treatment (p=0.69 and p=0.88, respectively). Attenuating effects of concomitant PPI treatment on platelet response to clopidogrel were restricted to the use of omeprazole. No attenuating effects on platelet response to clopidogrel were observed for pantoprazole or esomeprazole. Specifically designed and randomized clinical studies are needed to define the impact of concomitant PPI treatment on adverse events after percutaneous coronary intervention.
Keywords: Clopidogrel; proton pump inhibitors; platelet aggregation